2014
DOI: 10.1155/2014/925450
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Trials and Physiological Components Determining Yield Differences among Cowpea Varieties in Semiarid Zone of Nigeria

Abstract: Field trials were conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Maiduguri, Maiduguri (11 ∘ 47.840 N; 13 ∘ 12.021 E; elevation 319 m asl), in Borno State in semiarid zone of Nigeria during the 2010 and 2011 rainy seasons. The objectives of the study were to evaluate the agronomic performances of some improved cowpea varieties and to identify the physiological traits associated with high grain yield in the semiarid zone of Nigeria. The trial consisted of eight treatments, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In other words, even when considering the lowest CPD 0.25 , there was still a 25% probability that the simulated yield under either T 0 or T 1 treatment would still be greater than the average yield of 588.4 kg ha -1 (considering the calibrant Y2014). Furthermore, the yield range under both treatments was consistent with that reported by (Saka et al, 2018;Kamai, 2014) for semi-arid zone of Nigeria; but comparatively higher than that reported by (Kimiti et al, 2009) in the semi-arid zone of Eastern Kenya. The results of the five-years simulation study showed that, fertigation using human urine is a viable and stopgap indispensable option to obviate any shortcomings of inorganic fertilizer availability and supply for smallholder farmers in Africa.…”
Section: Biophysical Analysis: Grain Yield and Fertigationsupporting
confidence: 90%
“…In other words, even when considering the lowest CPD 0.25 , there was still a 25% probability that the simulated yield under either T 0 or T 1 treatment would still be greater than the average yield of 588.4 kg ha -1 (considering the calibrant Y2014). Furthermore, the yield range under both treatments was consistent with that reported by (Saka et al, 2018;Kamai, 2014) for semi-arid zone of Nigeria; but comparatively higher than that reported by (Kimiti et al, 2009) in the semi-arid zone of Eastern Kenya. The results of the five-years simulation study showed that, fertigation using human urine is a viable and stopgap indispensable option to obviate any shortcomings of inorganic fertilizer availability and supply for smallholder farmers in Africa.…”
Section: Biophysical Analysis: Grain Yield and Fertigationsupporting
confidence: 90%
“…Total seed protein content ranges from 23% to 32% of seed weight (Cruz et al, 2014). It is estimated that cowpea supplies about 40% of the daily protein requirements to most of the people in Nigeria (Kamai et al, 2014). Dry mature seeds are also suitable for boiling and canning.…”
Section: Introductionmentioning
confidence: 99%
“…The grain yield obtained in this study (1338 -1761 kg ha -1 ) though not up to the potential yield of the varieties (2000-2600 kg ha -1 ) (Nigerian seed portal, 2018) is a big improvement on the average of 350-450 kg ha -1 obtained on farmers' fields in Nigeria [KAMAI & al. 2014;OMOTOSO, 2014].…”
Section: Discussionmentioning
confidence: 93%